2019
DOI: 10.1016/j.syapm.2019.126015
|View full text |Cite
|
Sign up to set email alerts
|

Microvirga tunisiensis sp. nov., a root nodule symbiotic bacterium isolated from Lupinus micranthus and L. luteus grown in Northern Tunisia

Abstract: Three bacterial strains, LmiM8 T , LmiE10 and LluTb3, isolated from nitrogen-fixing nodules of Lupinus micranthus (Lmi strains) and L. luteus (Llu strain) growing in Northern Tunisia were analysed using genetic, phenotypic and symbiotic approaches. Phylogenetic analyses based on rrs and concatenated gyrB and dnaK genes suggested that these Lupinus strains constitute a new Microvirga species with identities ranging from 95 to 83% to its closest relatives Microvirga makkahensis, M. vignae, M. zambiensis, M. osse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 36 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…for a long time until Ardley et al (2012) reported the isolation and identification of three symbiotic Microvirga species from L. texensis and Listia angolensis root nodules. More recently, lupines were found to be nodulated by Microvirga strains in Tunisian, Moroccan, and American soils (Beligala et al, 2017;Msaddak et al, 2017Msaddak et al, , 2019Rejili et al, 2019;Missbah El Idrissi et al, 2020). Msaddak et al (2017) suggested that lupines would prefer Bradyrhizobium spp.…”
Section: Discussionmentioning
confidence: 99%
“…for a long time until Ardley et al (2012) reported the isolation and identification of three symbiotic Microvirga species from L. texensis and Listia angolensis root nodules. More recently, lupines were found to be nodulated by Microvirga strains in Tunisian, Moroccan, and American soils (Beligala et al, 2017;Msaddak et al, 2017Msaddak et al, , 2019Rejili et al, 2019;Missbah El Idrissi et al, 2020). Msaddak et al (2017) suggested that lupines would prefer Bradyrhizobium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the rhizobiome in GT0 was rich in microorganisms involved in significant processes commonly found in soil see Fig 2 . For example, certain species of bacteria promote plant growth, such as Methylobacterium soli (2%) and Microvirga ossetica (2%) (Chauhan et al 2015;Msaddak et al 2019). Furthermore, other bacteria play a role in the nitrogen cycle, such as Nitrososphaerales archaeon (2%) and Nitrosocosmicus oleophilus (1%), both of which contribute towards ammonia oxidation, as well as Nitrobacter vulgaris, which is a nitrite-oxidizing bacteria (1%) and Hyphomicrobium sp (9%) a denitrification bacterium that participate in the conversion of nitrates into nitrogen gas (Urakami).…”
Section: Rhizobiome Richness and Composition Of Plants Rt0 And Gt0mentioning
confidence: 99%
“…The genus Microvirga , proposed by Kanso and Patel in 2003 [1], belongs to the family Methylobacteriaceae , order Rhizobiales , class Alphaproteobacteria [2]. Members of Microvirga are widely distributed in nature, and have been isolated from various environments, including deep subsurface [1], soil [3, 4], forest soil [5], metal industry waste soil [6], desert soil [7], root nodule [8, 9], hot spring sediments [10], and human healthy skin [11]. Bacteria of this genus are important in soil and possess multiple ecological functions and application potentials [12, 13].…”
Section: Introductionmentioning
confidence: 99%